Antistatic surface protective film and optical component

By transferring the antistatic agent to the surface of the adhesive layer in the surface protective film, the problems of high peel voltage and time-lapse pollution are solved, and the surface protection effect of low peel voltage and low pollution is achieved, and the production efficiency and yield of the optical film are improved.

JP2025019216AInactive Publication Date: 2025-02-06ZACROS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024204518
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-06
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing surface protective film is prone to high peel voltage when peeled off, damages the circuit components of the liquid crystal display and increases the risk of contamination to the optical film, and the migration of antistatic agents over time leads to increased contamination.

Method used

The adhesive layer without antistatic agent is applied on one side of the substrate, and the release agent layer containing antistatic agent is applied on the other side. The antistatic agent is transferred to the surface of the adhesive layer by winding, forming an antistatic layer that exists only on the surface of the adhesive layer.

Benefits of technology

It effectively reduces the peel voltage, reduces contamination on the optical film, improves production efficiency and yield, and avoids damage to the circuit components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019216000001_ABST
    Figure 2025019216000001_ABST
Patent Text Reader

Abstract

To provide an antistatic surface protective film which can be bonded even to an optical film having unevenness thereon, causes little contamination on an adherend, does not change low contamination property to the adherent even after a lapse of time, and has excellent peeling antistatic performance without degradation with a lapse of time.SOLUTION: An antistatic surface protective film 5 in which a peeling agent layer 2 containing an antistatic agent 3 composed of an alkali metal salt and a peeling agent is provided on one surface of a transparent base material film 1 composed of a resin, and an adhesive layer 4 is provided on the other surface of the base material film 1, wherein the base material film 1 is wound into a roll shape with the adhesive layer 4 inside so that the peeling agent layer 2 and the adhesive layer 4 are brought into contact with each other, the component of the antistatic agent 3 composed of the alkali metal salt exists so as to be transferred to only the surface in the adhesive layer 4, and thereby a peeling charge voltage when the adhesive layer 4 is peeled from the adherend is +0.7 kV to -0.7 kV.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface protection film that is adhered to the surface of an optical component (hereinafter, sometimes referred to as an optical film). More specifically, the present invention relates to providing a surface protection film that causes little contamination of an adherend and does not change its contamination property over time, and an optical component using the same. The present invention also provides a surface protection film that keeps the peeling electrification voltage low when the surface protection film is peeled off, even if the constituent members of the polarizing plate, which is an optical component, are replaced (changing from a TAC film to an acrylic film or polyester film, or changing from a water-based adhesive to an ultraviolet-curable adhesive), and an optical component to which the surface protection film is adhered. In the present invention, the optical components refer to polarizing plates, retardation plates, lens films for displays, and the like. [Background technology]

[0002] When optical films such as polarizing plates, retardation plates, lens films for displays, anti-reflection films, hard coat films, transparent conductive films for touch panels, and other optical products such as displays using the same are manufactured and transported, a surface protective film is attached to the surface of the optical film to prevent the surface from being soiled or scratched in later processes. In order to improve work efficiency by eliminating the need to peel off the surface protective film and then reattach it, the appearance inspection of the optical film, which is a product, is sometimes performed with the surface protective film attached to the optical film.

[0003] Conventionally, a surface protection film having a pressure-sensitive adhesive layer on one side of a base film has been generally used in the manufacturing process of optical products to prevent scratches and dirt from adhering. The surface protection film is attached to an optical film via a pressure-sensitive adhesive layer having a weak adhesive strength. The pressure-sensitive adhesive layer has a weak adhesive strength so that the used surface protection film can be easily peeled off when peeled off and removed from the surface of the optical film, and the pressure-sensitive adhesive does not adhere to and remain on the optical film of the product, which is the adherend (so-called, to prevent the occurrence of adhesive residue).

[0004] In recent years, during the production process of liquid crystal display panels, there have been rare cases where the peeling charge voltage that is generated when peeling off and removing the surface protection film that has been laminated on top of the optical film has destroyed circuit components such as driver ICs that control the display screen of the liquid crystal display, or damaged the alignment of liquid crystal molecules. In addition, in order to reduce the power consumption of liquid crystal display panels, the driving voltage of liquid crystal materials has been lowered, and as a result, the breakdown voltage of driver ICs has also been lowered. Recently, there has been a demand for the peeling electrification voltage to be within the range of +0.7kV to -0.7kV.

[0005] In addition, conventional polarizing plates are manufactured by bonding triacetyl cellulose films (TAC films) to both sides of a polarizer made of iodine-impregnated polyvinyl alcohol (PVA) with a water-based adhesive to protect the polarizer, but in recent years, polarizing plates using acrylic films, cyclic polyolefin films, or polyester films instead of TAC films, and polarizing plates using ultraviolet-curing adhesives instead of water-based adhesives, have also come into use. Due to the change in the constituent materials of polarizing plates, there is also a problem that the peeling electrification voltage generated when peeling off and removing the surface protection film becomes higher than when using polarizing plates of conventional configurations.

[0006] In recent years, with the spread of 3D displays (stereoscopic displays), there are some in which an FPR (Film Patterned Retarder) film is laminated to the surface of an optical film such as a polarizing plate. The FPR film is laminated after peeling off the surface protective film that was laminated to the surface of the optical film such as a polarizing plate. However, if the surface of the optical film such as a polarizing plate is contaminated by the adhesive or antistatic agent used in the surface protective film, there is a problem that the FPR film is difficult to adhere. For this reason, surface protective films used for such applications are required to be ones that cause little contamination to the adherend.

[0007] On the other hand, some liquid crystal panel manufacturers have adopted a method for evaluating the fouling of a surface protective film on an adherend, in which the surface protective film attached to an optical film such as a polarizing plate is peeled off once, reattached in a state in which air bubbles are mixed in, heat-treated under a specified condition, and then the surface protective film is peeled off to observe the surface of the adherend. In this evaluation method, even if the surface contamination of the adherend is small, if there is a difference in the surface contamination of the adherend between the part where the air bubbles are mixed in and the part where the adhesive of the surface protective film was in contact, the traces of air bubbles (sometimes called air bubble stains) remain. Therefore, this is a very strict evaluation method for evaluating the fouling of the surface of the adherend. In recent years, there has been a demand for a surface protective film that can pass the judgment by such a strict evaluation method and that causes extremely little fouling on the surface of the adherend.

[0008] In order to prevent problems caused by high peeling electrification voltage that occurs when peeling the surface protective film from an adherend after the surface protective film is laminated to an optical film, a surface protective film has been proposed that uses a pressure-sensitive adhesive layer containing an antistatic agent to keep the peeling electrification voltage low.

[0009] For example, Patent Document 1 discloses a surface protection film that uses a pressure-sensitive adhesive made of an alkyltrimethylammonium salt, a hydroxyl group-containing acrylic polymer, and a polyisocyanate. Furthermore, Patent Document 2 discloses a pressure-sensitive adhesive composition comprising an ionic liquid and an acrylic polymer having an acid value of 1.0 or less, and pressure-sensitive adhesive sheets using the same. Furthermore, Patent Document 3 discloses an adhesive composition comprising an acrylic polymer, a polyether polyol compound, and an alkali metal salt treated with an anion-adsorbing compound, and a surface protection film using the same. Furthermore, Patent Document 4 discloses a pressure-sensitive adhesive composition comprising an ionic liquid, an alkali metal salt, and a polymer having a glass transition temperature of 0° C. or lower, and a surface protection film using the same. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2005-131957 A [Patent Document 2] JP 2005-330464 A [Patent Document 3] JP 2005-314476 A [Patent Document 4] JP 2006-152235 A Summary of the Invention [Problem to be solved by the invention]

[0011] In the surface protection films described in the above Patent Documents 1 to 4, an antistatic agent is added inside the adhesive layer. Therefore, the thicker the adhesive layer is, and the longer the time has passed since the surface protection film is attached to the adherend, the more the amount of antistatic agent that migrates from the adhesive layer to the adherend tends to increase. In addition, if the amount of antistatic agent that migrates to the adherend increases, the appearance quality of the optical film that is the adherend may decrease, or the adhesiveness of the FPR film may decrease when the FPR film is attached.

[0012] If the thickness of the adhesive layer is reduced in order to reduce the change over time of the antistatic agent that migrates from the adhesive layer to the adherend, other problems arise. For example, when the adhesive layer is used for an optical film having an uneven surface, such as a polarizing plate that has been antiglare-treated to prevent glare, the adhesive layer cannot conform to the unevenness of the optical film surface, causing air bubbles to be mixed in, or the adhesive area between the optical film and the adhesive layer is reduced, causing a decrease in adhesive strength, resulting in the surface protection film floating or peeling off during use.

[0013] Furthermore, if the amount of antistatic agent added to the adhesive layer is reduced in order to reduce the change over time of the antistatic agent that migrates from the adhesive layer to the adherend, the peeling electrostatic voltage generated when the surface protection film is peeled off and removed from the adherend increases, creating the risk of destruction of circuit components such as driver ICs or damage to the orientation of liquid crystal molecules.

[0014] The present invention has been made in consideration of the above circumstances, and has an object to provide a surface protection film to be attached to the surface of an optical film, which can be attached even to optical films having uneven surfaces, causes very little contamination of the adherend, and whose low contamination properties on the adherend do not change over time, and an optical component using the same. Another objective of the present invention is to provide a surface protection film that keeps the peeling electrification voltage low when the surface protection film is peeled off, even if the constituent materials of the polarizing plate, which is an optical component, are replaced (such as changing from a TAC film to an acrylic film or a polyester film, or changing from a water-based adhesive to an ultraviolet-curing adhesive), and an optical component using the same. [Means for solving the problem]

[0015] The present inventors have conducted extensive research to solve these problems. In order to reduce the staining of the adherend and to reduce the change in staining property over time, it is necessary to reduce the content of the antistatic agent, which is presumed to be the cause of staining the adherend. However, if the content of the antistatic agent is reduced, the peeling electrification voltage increases when the surface protection film is peeled off from the adherend. Therefore, the present inventors have investigated a method for suppressing the peeling electrification voltage when a surface protection film is peeled off from an adherend, without increasing the content of the antistatic agent.

[0016] The present inventors first prepared a surface protection film by laminating an adhesive layer on one side of a substrate by coating and drying an adhesive composition not containing an antistatic agent, and laminating a release agent layer containing an antistatic agent on the other side of the substrate. After this, the surface protection film was wound into a roll shape with the adhesive layer facing inward, whereby the components of the antistatic agent contained in the release agent layer were transferred to the surface of the adhesive layer and were present only on the surface of the adhesive layer. It was found that after this surface protection film was once attached to an optical film as an adherend, the peeling electrification voltage when peeled off from the adherend was kept low and the adherend was not easily contaminated, and thus the present invention was completed.

[0017] The surface protection film of the present invention is prepared by laminating an adhesive layer on one side of a substrate by coating and drying an adhesive composition not containing an antistatic agent, laminating a release agent layer containing an antistatic agent on the other side of the substrate, and then rolling the surface protection film into a roll with the adhesive layer facing inward, thereby transferring the components of the antistatic agent contained in the release agent layer to the surface of the adhesive layer. The technical idea of ​​the present invention is to keep the contamination of the adherend low when the surface protection film in this rolled state is unwound from the roll and attached to the adherend, and to keep the peeling electrification voltage low when the surface protection film is peeled off from the adherend, which is an optical film.

[0018] In order to solve the above problems, the present invention provides an antistatic surface protective film comprising a base film made of a transparent resin, on one side of which a release agent layer containing an antistatic agent composed of an alkali metal salt and a release agent is provided, and an adhesive layer is provided on the other side of the base film, the base film being wound into a roll shape with the adhesive layer on the inside so that the release agent layer and the adhesive layer are in contact with each other, the adhesive layer being an acrylic adhesive layer containing a crosslinked (meth)acrylate copolymer, and the component of the antistatic agent composed of the alkali metal salt is transferred and present only on the surface of the adhesive layer, thereby reducing the peeling electrification voltage when the adhesive layer is peeled off from an adherend.

[0019] The pressure-sensitive adhesive layer is preferably an acrylic pressure-sensitive adhesive layer containing a crosslinked (meth)acrylate copolymer.

[0020] The unfolding force of the surface protection film when wound into a roll is preferably 0.03 to 0.3 N / 50 mm.

[0021] In addition, the surface potential when the pressure-sensitive adhesive layer is peeled off from the adherend, that is, the optical film, is preferably +0.7 kV to -0.7 kV.

[0022] In addition, it is preferable that the base film is wound into a roll shape with the pressure-sensitive adhesive layer on the inside so that the release agent layer and the pressure-sensitive adhesive layer are in contact with each other.

[0023] The present invention also provides an optical component comprising the above-mentioned surface protection film bonded via the pressure-sensitive adhesive layer. Effect of the Invention

[0024] The surface protective film of the present invention is a surface protective film to be attached to the surface of an optical film, and can be attached even to an optical film having an uneven surface. Furthermore, according to the present invention, it is possible to provide a surface protection film that causes very little contamination of an adherend and does not change in its contamination property towards an adherend over time, and an optical component using the same. Furthermore, according to the present invention, it is possible to provide a surface protection film in which the peeling electrification voltage when peeling off the surface protection film is kept low even if the constituent materials of the polarizing plate, which is an optical component, are changed (such as changing from a TAC film to an acrylic film, a cyclic polyolefin film, or a polyester film, or changing from a water-based adhesive to an ultraviolet-curing adhesive), and an optical component using the same. In addition, the surface protection film wound into a roll of the present invention is a surface protection film in which a base film is wound into a roll with the adhesive layer on the inside so that the release agent layer and the adhesive layer are in contact with each other, and the component of the antistatic agent consisting of the alkali metal salt is transferred from the release agent layer to the surface of the adhesive layer and is present only on the surface of the adhesive layer. In other words, the present invention has the characteristic that, after a surface protection film is unwound from a roll-shaped surface protection film and laminated to an adherend, the peeling electrification voltage is reduced when the surface protection film is peeled off from the adherend, and there is little change over time in the peeling anti-static performance and little contamination of the adherend, thereby enabling the productivity of the optical component that is the adherend to be improved and the yield to be improved. [Brief description of the drawings]

[0025] [Figure 1] FIG. 2 is a conceptual cross-sectional view showing the surface protection film of the present invention wound into a roll. [Diagram 2] FIG. 2 is a conceptual cross-sectional view illustrating a state in which a release agent layer and a pressure-sensitive adhesive layer are in contact with each other when the surface protection film of the present invention is wound into a roll. [Diagram 3] FIG. 1 is a cross-sectional view showing one embodiment in which a surface protective film of the present invention is attached to an optical component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, the present invention will be described in detail based on the embodiments. Fig. 1 is a conceptual cross-sectional view showing a surface protection film 10 of the present invention in a rolled state. The surface protection film 10 in a rolled state shown on the right side of Fig. 1 is a surface protection film 5 according to the present invention wound into a roll with the pressure-sensitive adhesive layer 4 on the inside (a roll of surface protection film 5). The left side of Fig. 1 is a conceptual cross-sectional view showing the surface protection film 5 unwound from the roll in the direction of the arrow, enlarged in the thickness direction.

[0027] This surface protection film 5 has a release agent layer 2 containing an antistatic agent 3 made of an alkali metal salt on one side of a transparent base film 1, and an adhesive layer 4 formed on the other side of the base film 1. By winding the surface protection film 5 having the release agent layer 2 on one side of the base film 1 and the adhesive layer 4 on the other side of the base film into a roll with the adhesive layer 4 on the inside so that the release agent layer 2 and the adhesive layer 4 are in contact with each other, the component of the antistatic agent 3 contained in the release agent layer 2 is transferred to the surface of the adhesive layer 4, and a surface protection film 10 in a rolled state in which the component is present only on the surface of the adhesive layer 4 is obtained.

[0028] The substrate film 1 used in the surface protection film 5 according to the present invention is made of a transparent and flexible resin. This allows the surface protection film 5 to be attached to the optical component as the adherend, and the appearance of the optical component can be inspected. The film made of a transparent resin used as the substrate film 1 is preferably a polyester film such as polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, or polybutylene terephthalate. In addition to polyester films, films made of other resins can also be used as long as they have the necessary strength and optical suitability. The substrate film 1 may be a non-stretched film or a uniaxially or biaxially stretched film. The stretching ratio of the stretched film and the axial orientation angle formed by the crystallization of the stretched film may be controlled to a specific value. The thickness of the base film 1 used in the surface protection film 5 according to the present invention is not particularly limited, but is preferably about 12 to 100 μm, and more preferably about 20 to 75 μm for ease of handling. If necessary, the surface of the base film 1 may be subjected to a treatment for improving adhesion, such as surface modification by corona discharge or application of an anchor coating agent.

[0029] The release agent layer 2 formed on the surface protective film 5 according to the present invention is formed using a release agent containing an antistatic agent 3 made of an alkali metal salt. Examples of the release agent include silicone-based release agents, release agents containing a long-chain alkyl group, fluorine-based release agents, release agents made of a copolymer of silicone or fluorine with an organic material, and release agents made of a mixture of an organic resin and the release agent.

[0030] Examples of silicone-based release agents include known silicone-based release agents such as addition reaction type, condensation reaction type, cationic polymerization type, and radical polymerization type. Examples of products commercially available as addition reaction type silicone-based release agents include KS-776A, KS-847T, KS-779H, KS-837, KS-778, and KS-830 (manufactured by Shin-Etsu Chemical Co., Ltd.), SRX-211, SRX-345, SRX-357, SD7333, SD7220, SD7223, LTC-300B, LTC-350G, and LTC-310 (manufactured by Toray Dow Corning Co., Ltd.). Examples of products commercially available as condensation reaction type include SRX-290 and SYLOFF-23 (manufactured by Toray Dow Corning Co., Ltd.). Examples of commercially available cationic polymerization products include TPR-6501, TPR-6500, UV9300, VU9315, UV9430 (manufactured by Momentive Performance Materials, Inc.), and X62-7622 (manufactured by Shin-Etsu Chemical Co., Ltd.). Examples of commercially available radical polymerization products include X62-7205 (manufactured by Shin-Etsu Chemical Co., Ltd.). In addition, silicone resin (a silicon resin consisting of R3SiO1 / 2 units and SiO4 / 2 units), silica, ethyl cellulose, etc. may be added to these release agents to adjust the release performance.

[0031] Examples of long-chain alkyl group-containing release agents include known long-chain alkyl group-containing aminoalkyd resins, long-chain alkyl group-containing acrylic resins, long-chain aliphatic pendant resins (reaction products of at least one active hydrogen-containing polymer selected from the group of compounds consisting of polyvinyl alcohol, ethylene / vinyl alcohol copolymers, polyethyleneimine, and hydroxyl group-containing cellulose derivatives with long-chain alkyl group-containing isocyanates), etc. The release agent may be one that undergoes a curing reaction by adding a curing agent and an ultraviolet initiator, or one that solidifies by volatilizing the solvent. The "long-chain alkyl group" is preferably an alkyl group having 8 to 30 carbon atoms, and may be one having 10 or more, 12 or more, 18 or less, or 24 or less carbon atoms, and among these, a straight-chain alkyl group is preferable. Specific examples include one or more alkyl groups selected from a decyl group, an undecyl group, a lauryl group, a dodecyl group, a tridecyl group, a myristyl group, a tetradecyl group, a pentadecyl group, a cetyl group, a palmityl group, a hexadecyl group, a heptadecyl group, a stearyl group, an octadecyl group, a nonadecyl group, an icosyl group, a docosyl group, and the like. Examples of commercially available products as long-chain alkyl group-containing release agents include ASIO RESIN (registered trademark) RA-30 manufactured by ASIO Sangyo Co., Ltd., PIEROIL (registered trademark) 1010, PIEROIL 1010S, PIEROIL 1050, and PIEROIL HT manufactured by Ipposha Yushi Kogyo Co., Ltd., REZEM N-137 manufactured by Chukyo Yushi Co., Ltd., EXPEPARL (registered trademark) PS-MA manufactured by Kao Corporation, and TESFAINE (registered trademark) 303 manufactured by Hitachi Chemical Co., Ltd.

[0032] Examples of fluorine-based release agents include perfluoroalkyl group-containing vinyl ether polymers and coating agents in which a fluorine resin such as tetrafluoroethylene or trifluoroethylene is dispersed in a binder resin.

[0033] Examples of release agents made of a copolymer of silicone or fluorine and an organic material include graft copolymerized acrylic resin with silicone or fluorine resin, copolymerized alkyd resin with silicone, etc. Examples of products that are commercially available as release agents made of a copolymer of silicone or fluorine and an organic material include CYMAC (registered trademark) manufactured by Toa Gosei Co., Ltd. and TESFIN (registered trademark) manufactured by Hitachi Kasei Polymer Co., Ltd.

[0034] Examples of the organic resin used in the release agent consisting of a mixture of an organic resin and the release agent include polyester resin, epoxy resin, acrylic resin, urethane resin, phenol resin, alkyd resin, aminoalkyd resin, polyolefin resin (polyethylene, polypropylene, cyclic polyolefin), polyvinyl alcohol, cellulose-based resin, and melamine resin.

[0035] The release agent used in the surface protection film of the present invention must be selected in consideration of the spreading force of the surface protection film. In the surface protection film of the present invention, the release agent layer and the adhesive layer are in contact with each other in the surface protection film wound in a roll. When the surface protection film of the present invention is used, it is unwound from the surface protection film wound in a roll. If the spreading force when unwounding the surface protection film is large, there is a concern that the workability when unwounding the surface protection film is poor, or the surface of the adhesive layer of the surface protection film is roughened (the surface is not smooth but uneven), which makes it easy to trap air bubbles when it is attached to the adherend. On the other hand, if the spreading force when unwounding the surface protection film from the surface protection film wound in a roll is too small, the roll shape of the surface protection film is distorted during storage or transportation, or when the surface protection film is used, the surface protection film is unwound more than necessary, which may cause wrinkles during the bonding operation with the adherend, or the bonded product of the surface protection film and the adherend may curl. For this reason, the unfolding force of the surface protection film in a rolled state is preferably 0.03 to 0.3 N / 50 mm. A release agent that allows the surface protection film to unfold at the above-mentioned force may be selected depending on the pressure-sensitive adhesive used.

[0036] In addition, when the surface protection film 5 according to the present invention is attached to an optical component 6 via the adhesive layer 4 (see FIG. 3), the release agent layer 2 is exposed on the surface of the surface protection film 5. However, when the surface protection film is used to protect a polarizing plate, the polarizing plate to which the surface protection film is attached may be cut to a predetermined size at the time of shipping the polarizing plate, and a plurality of polarizing plates with the cut surface protection film may be stacked. In this case, if the release agent layer is not slippery, a problem occurs in that a plurality of polarizing plates with the surface protection film are picked up when one polarizing plate with the surface protection film is picked up. In addition, if the release agent layer is too slippery, a problem occurs in that the polarizing plates slip when a plurality of polarizing plates with the surface protection film are stacked, making it difficult to stack them. For this reason, when selecting a release agent constituting the release agent layer, slipperiness must also be taken into consideration.

[0037] The antistatic agent 3 contained in the release agent layer 2 is preferably one that has good dispersibility in the release agent solution and does not inhibit hardening of the release agent. In addition, since the components of the antistatic agent 3 contained in the release agent layer 2 are transferred to the surface of the adhesive layer 4 in contact with the release agent layer 2 to impart an antistatic function to the surface of the adhesive layer 4, an antistatic agent that does not react with the release agent is preferable. As such an antistatic agent, an alkali metal salt is preferable.

[0038] Examples of the alkali metal salt include metal salts of lithium, sodium, and potassium. + , Na + , K + and a cation selected from Cl - , Br - , I - , B.F. 4 - , P.F. 6 - , SCN - , ClO 4 - , C.F. 3 SO 3 - , (CF 3 SO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - , (CF 3 SO 2 ) 3 C - Metal salts composed of anions selected from the following are preferably used. Specific examples of alkali metal salts include LiBr, LiI, and LiBF. 4 , LiPF 6 , LiSCN, LiClO 4 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, Li(C 2 F 5 SO 2 ) 2 N, Li(CF 3SO 2 ) 3 C and other lithium salts are preferably used. These alkali metal salts may be used alone or in combination of two or more. In order to stabilize the ionic substance, a compound containing a polyoxyalkylene structure may be added.

[0039] The amount of antistatic agent added to the release agent varies depending on the type of antistatic agent and the degree of affinity with the release agent, but may be set in consideration of the desired peeling charge voltage, staining property to the adherend, adhesive properties, etc. when the surface protective film is peeled off from the adherend. When the release agent is a silicone-based release agent, the mixing ratio (weight ratio) of the silicone-based release agent and the antistatic agent is, for example, preferably 5 to 100 of the antistatic agent as a solid content to 100 of the silicone-based release agent, and more preferably 5 to 60. If the amount of the antistatic agent added in terms of solid content is less than 5 to 100 of the silicone-based release agent as a solid content, the amount of the antistatic agent transferred to the surface of the adhesive layer is also reduced, making it difficult for the adhesive to exhibit its antistatic function. Furthermore, if the amount of antistatic agent added, calculated as solid content, exceeds 100 per 100 solid content of the silicone-based release agent, the components of the silicone-based release agent will be transferred to the surface of the adhesive layer along with the antistatic agent, which may reduce the adhesive properties of the adhesive.

[0040] The release agent layer 2 is composed of at least a release agent and an antistatic agent that does not react with the release agent. There is no particular limitation on the method of mixing the release agent and the antistatic agent. Any method may be used, such as a method of adding an antistatic agent to the release agent, mixing the antistatic agent, and then adding and mixing a catalyst for hardening the release agent, a method of diluting the release agent with an organic solvent in advance, adding and mixing an antistatic agent and a catalyst for hardening the release agent, and a method of diluting the release agent with an organic solvent in advance, adding and mixing a catalyst, and then adding and mixing an antistatic agent. In addition, the release agent layer 2 may contain, as necessary, an adhesion improver such as a silane coupling agent, a material that assists the antistatic effect such as a compound containing a polyoxyalkylene group, a material that imparts printability such as a cellulose-based compound, a material that adjusts slipperiness, and the like.

[0041] A known method may be used to form the release agent layer 2 on the surface of the base film 1. Specifically, known coating methods such as gravure coating, Mayer bar coating, and air knife coating can be used.

[0042] In the adhesive layer 4 formed on the surface protection film 5 according to the present invention, the component of the antistatic agent 3 contained in the release agent layer 2 is not present inside (other than on the surface) the adhesive layer 4, but only on the surface of the adhesive layer 4. This makes it possible to suppress the change over time in the antistatic performance upon peeling of the surface protection film 5 and the contamination of the adherend. The pressure-sensitive adhesive layer 4 formed on the surface protection film 5 according to the present invention is not particularly limited as long as it is an adhesive layer that adheres to the surface of an adherend, can be easily peeled off after use, and does not easily contaminate the adherend. Considering that durability is required after the surface protection film 5 according to the present invention is attached to an optical film, it is preferable that the pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive layer formed by crosslinking a (meth)acrylate copolymer.

[0043] Examples of the (meth)acrylate copolymer include copolymers obtained by copolymerizing a main monomer such as n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, etc. with a comonomer such as acrylonitrile, vinyl acetate, methyl methacrylate, ethyl acrylate, etc., and a functional monomer such as acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxybutyl acrylate, glycidyl methacrylate, N-methylol methacrylamide, etc. In the (meth)acrylate copolymer, the main monomer and other monomers may all be (meth)acrylates, or the copolymer may contain one or more monomers other than (meth)acrylates as monomers other than the main monomer.

[0044] In addition, a compound containing a polyoxyalkylene group may be copolymerized or mixed with the (meth)acrylate copolymer. Examples of copolymerizable compounds containing a polyoxyalkylene group include polyethylene glycol (400) monoacrylate, polyethylene glycol (400) monomethacrylate, methoxypolyethylene glycol (400) acrylate, methoxypolyethylene glycol (400) methacrylate, polypropylene glycol (400) monoacrylate, polypropylene glycol (400) monomethacrylate, methoxypolypropylene glycol (400) acrylate, and methoxypolypropylene glycol (400) methacrylate. By copolymerizing these monomers containing a polyoxyalkylene group with the main monomer or functional monomer of the (meth)acrylate copolymer, a pressure-sensitive adhesive consisting of a copolymer containing a polyoxyalkylene group can be obtained.

[0045] As the compound containing a polyoxyalkylene group that can be mixed with the (meth)acrylate copolymer, a (meth)acrylate copolymer containing a polyoxyalkylene group is preferable, and a polymer of a (meth)acrylic monomer containing a polyoxyalkylene group is more preferable, and examples thereof include polymers of polyethylene glycol (400) monoacrylate, polyethylene glycol (400) monomethacrylate, methoxypolyethylene glycol (400) acrylate, methoxypolyethylene glycol (400) methacrylate, polypropylene glycol (400) monoacrylate, polypropylene glycol (400) monomethacrylate, methoxypolypropylene glycol (400) acrylate, and methoxypolypropylene glycol (400) methacrylate. By mixing these compounds containing a polyoxyalkylene group with the (meth)acrylate copolymer, a pressure-sensitive adhesive to which a compound containing a polyoxyalkylene group is added can be obtained.

[0046] Examples of the curing agent added to the adhesive layer 4 include crosslinking agents that crosslink the (meth)acrylate copolymer, such as isocyanate compounds, epoxy compounds, melamine compounds, metal chelate compounds, etc. Examples of the tackifier include rosin-based, coumarone-indene-based, terpene-based, petroleum-based, and phenol-based agents.

[0047] The thickness of the pressure-sensitive adhesive layer 4 formed on the surface protection film 5 according to the present invention is not particularly limited, but is preferably about 5 to 40 μm, and more preferably about 10 to 30 μm. It is preferable that the pressure-sensitive adhesive layer 4 has a weak adhesive strength, that is, a peel strength (adhesive strength) of the surface protection film to the surface of the adherend of about 0.03 to 0.3 N / 25 mm, because this provides excellent operability when peeling the surface protection film from the adherend.

[0048] The method for forming the pressure-sensitive adhesive layer 4 on the base film 1 of the surface protection film 5 according to the present invention may be a known method and is not particularly limited. Specifically, known coating methods such as reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating can be used.

[0049] The surface protective film 5 according to the present invention having the above configuration preferably has a surface potential of +0.7 kV to -0.7 kV when the pressure-sensitive adhesive layer 4 is peeled off from the adherend, which is the optical film. Furthermore, the surface potential is more preferably +0.5 kV to -0.5 kV, and particularly preferably +0.2 kV to -0.2 kV. This surface potential can be adjusted by adjusting the type and amount of the antistatic agent 3 contained in the release agent layer 2. The type and amount of the antistatic agent 3 in the release agent layer 2 may be adjusted in consideration of the surface contamination of the adherend, which is the optical film, after the surface protective film 5 is peeled off from the adherend, which is the optical film.

[0050] FIG. 2 is a conceptual cross-sectional view showing a state in which the release agent layer 2 and the adhesive layer 4 are in contact with each other when the surface protection film 5 of the present invention is wound into a roll. The surface protection film 5 is formed by forming the release agent layer 2 containing the antistatic agent 3 on one side of the base film 1 and the adhesive layer 4 not containing the antistatic agent 3 on the other side of the base film 1, and is wound into a roll with the adhesive layer 4 facing inward to form the surface protection film 10, whereby the release agent layer 2 and the adhesive layer 4 are in contact with each other in the radial direction of the roll body. As a result, a part of the component of the antistatic agent (reference numeral 3) contained in the release agent layer 2 is transferred to the surface of the adhesive layer 4. FIG. 3 shows a state in which the surface protection film 5 unrolled from the surface protection film 10 thus obtained in a rolled state is attached to an optical component 6. By transferring the component of the antistatic agent 3 from the release agent layer 2 to the surface of the adhesive layer 4, the peeling electrification voltage when the surface protective film 5 is attached to the adherend and then peeled off from the adherend is reduced compared to the adhesive layer 4 before the component of the antistatic agent 3 is transferred. The peeling electrification voltage when peeling off the surface protective film 5 of FIG. 1 from the adherend can be measured by a known method. For example, after the surface protective film 5 is attached to an adherend such as a polarizing plate, the surface protective film 5 is peeled off at a peeling speed of 40 m per minute using a high-speed peel tester (manufactured by Tester Sangyo Co., Ltd.), and the maximum absolute value of the surface potential when the surface protective film 5 is measured every 10 ms using a surface potential meter (manufactured by Keyence Corporation) is measured as the peeling electrification voltage (kV).

[0051] In the surface protection film 10 wound in a roll according to the present invention, when the surface protection film 5 unwound from the roll is attached to an adherend, the antistatic agent 3 transferred to the surface of the adhesive layer 4 comes into contact with the surface of the adherend. This makes it possible to keep the peeling electrification voltage low when the surface protection film 5 is peeled off from the adherend again. In addition, in the surface protection film 10 wound in a roll according to the present invention, the release agent layer 2 is on the outside and the adhesive layer 4 is on the inside, so that the surface of the adhesive layer 4 is protected without being exposed in the rolled state. Even after the surface protection film 5 is unwound from the roll, the release agent layer 2 is integrated with the base film 1, so there is no need to remove or discard the release agent layer 2.

[0052] FIG. 3 is a cross-sectional view showing an optical component 7 with a surface protective film as one of the embodiments in which the surface protective film 5 of the present invention is laminated to an optical component. The optical component 7 with a surface protective film is obtained by unrolling the surface protective film 5 of the present invention from the surface protective film 10 wound in a roll shape and laminating it to the optical component 6, which is an adherend, via the pressure-sensitive adhesive layer 4. Examples of the optical component 6 include optical films such as a polarizing plate, a retardation plate, a lens film, a polarizing plate that also serves as a retardation plate, and a polarizing plate that also serves as a lens film. Such optical components are used as components of liquid crystal display devices such as liquid crystal display panels, optical devices for various instruments, and the like. Examples of the optical components include optical films such as anti-reflection films, hard coat films, and transparent conductive films for touch panels.

[0053] When the surface protective film 5 of the present invention is unwound from the surface protective film 10 wound in a roll and attached to an optical component (optical film) as an adherend, and then the surface protective film 5 is peeled off and removed from the adherend, the peeling electrification voltage can be suppressed to a sufficiently low level. Therefore, there is no risk of damaging circuit components such as driver ICs, TFT elements, and gate line driving circuits, and the production efficiency in the process of manufacturing liquid crystal display panels and the like can be improved and the reliability of the production process can be maintained. EXAMPLES

[0054] Next, the present invention will be described in more detail with reference to examples.

[0055] Example 1 (Preparation of surface protection film) 3.125 parts by weight of a release agent containing a long chain alkyl group (manufactured by Hitachi Chemical Co., Ltd., product name: Tesfine 303), 7.5 parts by weight of a 10% ethyl acetate solution of lithium bis(fluorosulfonyl)imide, 89.375 parts by weight of a 50:50 mixed solvent of toluene and ethyl acetate, and 0.09 parts by weight of a catalyst (manufactured by Hitachi Chemical Co., Ltd., product name: Dryer 900) were mixed and stirred to prepare a coating material for forming the release agent layer of Example 1. On the other hand, 100 parts by weight of a 40% ethyl acetate solution of an adhesive consisting of a copolymer of 90 parts by weight of 2-ethylhexyl acrylate, 7 parts by weight of methoxypolyethylene glycol (400) methacrylate, and 3 parts by weight of 2-hydroxyethyl acrylate was stirred and mixed with 2 parts by weight of an isocyanate-based curing agent (Coronate (registered trademark) HX manufactured by Tosoh Corporation) to prepare the adhesive composition of Example 1. The coating material for forming the release agent layer of Example 1 was applied to the surface of a polyethylene terephthalate film having a thickness of 38 μm using a Mayer bar so that the thickness after drying was 0.2 μm, and the coating material was dried in a hot air circulation oven at 120 ° C for 1 minute to form a release agent layer. Next, the prepared adhesive composition was applied to the surface of the polyethylene terephthalate film on which the release agent layer was not formed so that the thickness after drying was 20 μm, and then the coating material was dried in a hot air circulation oven at 100 ° C for 2 minutes to form an adhesive layer. Thereafter, the obtained film having the release agent layer formed on one side of the base film and the adhesive layer formed on the other side was rolled up with the adhesive layer on the inside so that the release agent layer and the adhesive layer were in contact with each other. The obtained adhesive film rolled up in a roll was kept warm in an environment of 40 ° C for 5 days to harden the adhesive layer, and the surface protection film in the rolled state of Example 1 was obtained.

[0056] Example 2 8.33 parts by weight of a release agent containing a long chain alkyl group (manufactured by Ipposha Yushi Kogyo Co., Ltd., product name: Piroyl HT), 7.5 parts by weight of a 10% ethyl acetate solution of lithium bis(trifluoromethanesulfonyl)imide, and 84.17 parts by weight of a 50:50 mixed solvent of toluene and ethyl acetate were mixed and stirred to prepare a paint for forming the release agent layer of Example 2. A surface protection film in a roll shape of Example 2 was obtained in the same manner as in Example 1, except that the paint for forming the release agent layer was changed to the paint of Example 2.

[0057] Example 3 14 parts by weight of a 10% toluene solution of ethyl cellulose (manufactured by Dow Chemical Company, product name: Ethocel FP100), 0.67 parts by weight of an addition reaction type silicone (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-345), 7.5 parts by weight of a 10% ethyl acetate solution of lithium bis(fluorosulfonyl)imide, 77.83 parts by weight of a 1:1 mixed solvent of toluene and ethyl acetate, and 0.07 parts by weight of a 10% toluene solution of platinum catalyst (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-212) were mixed and stirred and mixed to prepare a coating material for forming the release agent layer of Example 3. A surface protection film in a rolled state of Example 3 was obtained in the same manner as in Example 1, except that the coating material for forming the release agent layer was changed to the coating material of Example 3.

[0058] Example 4 5 parts by weight of addition reaction type silicone (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-345), 7.5 parts by weight of a 10% ethyl acetate solution of lithium bis(fluorosulfonyl)imide, 87.5 parts by weight of a 1:1 mixed solvent of toluene and ethyl acetate, and 0.05 parts by weight of a platinum catalyst (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-212) were mixed and stirred / mixed to prepare a coating material for forming the release agent layer of Example 4. A surface protection film in a roll shape of Example 4 was obtained in the same manner as in Example 1, except that the coating material for forming the release agent layer was changed to the coating material of Example 4.

[0059] Comparative Example 1 A surface protection film of Comparative Example 1 in a rolled state was obtained in the same manner as in Example 1, except that the antistatic agent lithium bis(fluorosulfonyl)imide was not added.

[0060] Comparative Example 2 A surface protection film in a rolled state of Comparative Example 2 was obtained in the same manner as in Example 1, except that instead of adding lithium bis(fluorosulfonyl)imide to the release agent, 0.67 parts by weight of lithium bis(fluorosulfonyl)imide was added to the adhesive side per 100 parts by weight of a 40% ethyl acetate solution.

[0061] The evaluation test methods and results are shown below. <Method for measuring the spreading force of a surface protection film> From the surface protection film wound in a roll, a sample of the unwound surface protection film was cut in a state of overlapping two layers, and cut into a piece of 50 mm width and 150 mm length. Under a test environment of 23°C x 50% RH, a tensile tester was used to measure the strength when peeled in a 180° direction at a peeling speed of 300 mm / min, and this was taken as the spreading force (N / 50 mm) of the surface protection film.

[0062] (Surface resistivity of release layer and adhesive layer) The surface resistivity (Ω / □) of the release agent layer and adhesive layer of a surface protection film sample that was unwound from the roll was measured using a high-performance high resistivity meter (Hiresta (registered trademark)-UP, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) at an applied voltage of 100 V and a measurement time of 30 seconds.

[0063] <Method for measuring adhesive strength of surface protection film> The adherend was an anti-glare low-reflection treated polarizing plate (AG-LR polarizing plate) in which an acrylic film was attached to a polarizer (polyvinyl alcohol film containing iodine) using a UV-curable adhesive. This polarizing plate was attached to the surface of a glass plate using a double-sided adhesive tape using a laminating machine. After that, a surface protection film cut to a width of 25 mm was attached to the acrylic film on the surface of the polarizing plate, and the plate was stored for one day under a test environment of 23°C x 50% RH. Then, the strength was measured when the surface protection film was peeled off in the direction of 180° at a peeling speed of 300 mm / min using a tensile tester, and this was taken as the adhesive strength (N / 25 mm).

[0064] <Method for measuring the peeling electrification voltage of surface protection film> The anti-glare low reflection treated polarizing plate (AG-LR polarizing plate) was used as the adherend, which was made by laminating an acrylic film to a polarizer (polyvinyl alcohol film containing iodine) using an ultraviolet curing adhesive. This polarizing plate was laminated to the surface of a glass plate using a laminating machine with a double-sided adhesive tape. Then, a surface protection film cut to a width of 25 mm was laminated on the acrylic film on the surface of the polarizing plate, and the plate was stored for one day under a test environment of 23°C x 50% RH. Then, the surface protection film was peeled off at a peeling speed of 40 m per minute using a high-speed peeling tester (manufactured by Tester Sangyo Co., Ltd.), and the maximum absolute value of the surface potential when the surface potential was measured every 10 ms using a surface potential meter (manufactured by Keyence Corporation) was taken as the peeling electrification voltage (kV).

[0065] <Method for checking surface contamination of surface protection film> The anti-glare low reflection treated polarizing plate (AG-LR polarizing plate) was used as the adherend, which was made by bonding an acrylic film to a polarizer (polyvinyl alcohol film containing iodine) using an ultraviolet curing adhesive. This polarizing plate was bonded to the surface of a glass plate using a bonding machine with a double-sided adhesive tape. After that, a surface protection film cut to a width of 25 mm was bonded to the acrylic film on the surface of the polarizing plate, and the plate was stored for 3 days and 30 days under a test environment of 23°C x 50% RH. After that, the surface protection film was peeled off, and the presence or absence of contamination on the surface of the polarizing plate was visually observed to confirm the surface contamination. As the criterion for the surface contamination, the case where no contamination was transferred to the polarizing plate was marked as (○), and the case where contamination was confirmed to be transferred to the polarizing plate was marked as (×).

[0066] The results of measurements of the obtained surface protection films in a rolled state of Examples 1 to 4 and Comparative Examples 1 and 2 are shown in Table 1. "2EHA" means 2-ethylhexyl acrylate, "HEA" means 2-hydroxyethyl acrylate, "#400G" means methoxypolyethylene glycol (400) methacrylate, "AS agent (1)" means lithium bis(fluorosulfonyl)imide, "AS agent (2)" means lithium bis(trifluoromethanesulfonyl)imide, "303" means Tesfine 303, "Dryer" means Dryer 900, "HT" means Pieloyl HT, "FP-100" means Ethocel FP100, "SRX-345" means SRX-345, "SRX-211" means SRX-211, and "SRX212" means platinum catalyst SRX-212. The surface resistivity "3.7E11" is 3.7×10 11 "Over-range" means exceeding the measurement limit of the measuring instrument, and is 1.0×10 13 This means Ω / □ or more.

[0067] [Table 1]

[0068] The measurement results shown in Table 1 reveal the following: The surface protection films in the rolled state according to Examples 1 to 4 of the present invention have an appropriate adhesive strength and do not contaminate the surface of the adherend when unwound from the roll for use. Moreover, even if the adherend is a polarizing plate using an acrylic film, the peeling electrification voltage when peeling the surface protection film from the adherend after it is once attached to the adherend is low. On the other hand, the surface protection film in the rolled state of Comparative Example 1, in which no antistatic agent was added to the release agent layer, showed a high peeling electrification voltage when the surface protection film was unwound from the roll and once attached to the adherend and then peeled off from the adherend. Also, the surface protection film in the rolled state of Comparative Example 2, in which an antistatic agent was contained in the pressure-sensitive adhesive layer instead of the release agent layer, showed a low and favorable peeling electrification voltage when the surface protection film was unwound from the roll and once attached to the adherend and then peeled off from the adherend, but there was a lot of contamination of the adherend after the surface protection film was peeled off. That is, it is difficult for the surface protection films in the rolled state of Comparative Examples 1 and 2 to simultaneously achieve a reduction in peeling electrification voltage and low contamination of the adherend. On the other hand, the surface protection films in the rolled state of Examples 1 to 4, in which an antistatic agent was added to the release agent layer and the components of the antistatic agent were transferred only to the surface of the pressure-sensitive adhesive layer, were able to effectively achieve both a reduction in peeling electrification voltage and low contamination of the adherend. [Industrial Applicability]

[0069] The surface protective film of the present invention can be used to protect the surface by being attached to the surface of optical components, etc., in the production process of optical films such as polarizing plates, retardation plates, lens films, antireflection films, hard coat films, transparent conductive films, and other various optical components, etc. In addition, the surface protective film of the present invention can suppress the peeling electrification voltage generated when peeling the surface protective film from the adherend after being attached to the adherend, optical components (optical films), and can reduce the change over time in the peeling antistatic performance and the contamination of the adherend, improving the yield of the production process, and is of great industrial utility. [Explanation of symbols]

[0070] 1...base film, 2...release agent layer, 3...antistatic agent, 4...adhesive layer, 5...surface protection film, 6...optical component (optical film), 7...optical component with surface protection film, 10...surface protection film wound into a roll.

Claims

1. An antistatic surface protection film comprising a base film made of a transparent resin, a release agent layer containing an antistatic agent made of an alkali metal salt and a release agent provided on one side of the base film, and a pressure-sensitive adhesive layer provided on the other side of the base film, the base film is wound into a roll shape with the pressure-sensitive adhesive layer on the inside so that the release agent layer and the pressure-sensitive adhesive layer are in contact with each other, the pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive layer containing a crosslinked (meth)acrylate copolymer, The antistatic surface protective film is characterized in that the antistatic agent component consisting of the alkali metal salt is transferred and present only on the surface of the pressure-sensitive adhesive layer, and thus the peeling electrification voltage when the pressure-sensitive adhesive layer is peeled off from an adherend is +0.7 kV to -0.7 kV.

2. 2. An optical part comprising the antistatic surface protective film according to claim 1 attached via the pressure-sensitive adhesive layer.

Citation Information

Patent Citations

  • Acrylic self-adhesive composition for surface protective film of optical member and surface protective film of optical member using the same

    JP2011236268A

  • Surface protective film and optical component with surface protective film affixed

    JP2015024630A

  • Surface protection film, method for manufacturing surface protection film, and optical film

    JP2015120337A

  • Adhesive film and method of using the same

    JP2015140365A

  • Surface protecting film and optical component whereon it is stuck

    JP2005131957A